1988
DOI: 10.1136/bjsm.22.4.132
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, maximal power output and fatigue.

Abstract: The purpose of this investigation was to determine the effects of caffeine ingestion on maximal power output and fatigue during short term, high intensity exercise. Nine adult males performed 15 s maximal exercise bouts 60 min after ingestion of caffeine (7 mg.kg-1) or placebo. Exercise bouts were carried out on a modified cycle ergometer which allowed power output to be computed for each one-half pedal stroke via microcomputer. Peak power output under caffeine conditions was not significantly different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
0
10

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 16 publications
7
40
0
10
Order By: Relevance
“…By comparison, this study tested the isometric endurance of subjects aged Ն70 yr, generating a constant force corresponding to 50% of their maximal arm flexion strength. Similar to findings in studies of younger persons (19,43), caffeine had no effect on maximal voluntary strength. The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times.…”
Section: Discussionsupporting
confidence: 79%
“…By comparison, this study tested the isometric endurance of subjects aged Ն70 yr, generating a constant force corresponding to 50% of their maximal arm flexion strength. Similar to findings in studies of younger persons (19,43), caffeine had no effect on maximal voluntary strength. The reported effect of caffeine on psychomotor function is somewhat conflicting (21,24,35), but, in this study, there was no indication that caffeine improved either reaction or movement times.…”
Section: Discussionsupporting
confidence: 79%
“…the 105%VO2max test and inversely decreased it in the IG test. In humans, whether caffeine enhances exercise performance during incremental exercise [13,15] and intense short-duration exercise [18,33] remains unclear. Furthermore, in humans the habituation and tolerance to caffeine as well as the training fitness state should affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…ergogenic effects of caffeine during high intensity, shortterm exercise [18,33] or incremental exercise [6,15] remain unclear. Tarnopolsky [31] concluded that caffeine would not be ergogenic in the intense exercise that lasts less than 15 min.…”
mentioning
confidence: 99%
“…Entretanto, a utilização da cafeína como recurso ergogênico em atividades de alta intensidade e curta duração, tem gerado ao longo dos últimos anos controvérsias a cerca da sua eficácia (ANSELME et al, 1992;BRUCE et al, 2000;COLLOMP et al, 1991;DOHERTY, 1998;GREER et al, 1998;JACKMAN et al, 1996;WILLIAMS et al, 1988;WYSS et al, 1986).…”
Section: Introductionunclassified